Empowering Inclusive Knowledge Societies: Integrating Media Literacy in University-Level Language Education in the USA and Kazakhstan - Perizat Yelubayeva; Lauren Flenniken; Todd Owen; Zhanargul Gabdullina (Journal of Central Asian Studies)
This research explores the integration of media literacy into university-level language education. It compares the perspectives of language educators in the USA and Kazakhstan, focusing on their potential to empower inclusive knowledge societies by fostering equitable access to critical thinking and media engagement skills. The study aims to uncover how educators perceive media literacy's importance, the extent of its integration, and the social and institutional challenges they face. Employing a comparative survey-based approach, data was collected from the USA and Kazakhstan language educators, addressing the significance of media literacy, integration practices, barriers, and benefits. The data offered a comparative analysis of the two educational contexts. Findings reveal significant differences between the countries. Educators in the USA report advanced integration of media literacy, supported by institutional frameworks, while their counterparts in Kazakhstan face challenges like resource limitations, insufficient training, and digital inequality. Despite these barriers, educators in both contexts recognize media literacy as a transformative tool for fostering critical thinking, social awareness, and active citizenship. This comparative analysis illuminates the potential of media literacy to bridge digital divides, promote equitable education, and prepare students for active participation in sustainable, knowledge-sharing communities.